Biographical connections: Experiences as sources of legitimate knowledge in qualitative research - Telles, João A. [UNESP] (Taylor & Francis, 2000)
In the narrative that follows, the author establishes biographical connections between a few marker events of his life history and the research topic he set himself to explore: teachers' critical awareness of language. By using a bricolage of qualitative research methods (narrative inquiry, hermeneutic phenomenology, heuristic research and arts-based research), the narrator illustrates the use of experiences as sources of legitimate knowledge in the research process. A composite portrait - a synthesis of the essential descriptions and meaningful interpretations of his experiences - is, then, presented in the form of a poem that illustrates a process of personal and professional growth and of becoming increasingly and critically aware of the construction of a teacher-self. © 2000, Taylor & Francis Group, LLC. All rights reserved.